Kulliyah of Islamic Revealed Knowledge and Human Sciences, IIUM: a successful story of integration of Islamic and human sciences - Ahmad H.Osman, Rahmah (2017)
This paper studies the case of integration of Islamic and Human Sciences in theory and practice by highlighting the achievements of International Islamic University Malaysia (IIUM). This paper follows qualitative descriptive analysis approach. It highlights that IIUM is the pioneering institution in cultivating the idea of integration, and the Kulliyah (Faculty) of Islamic Revealed Knowledge and Human Sciences (KIRKHS) plays a vital role in that process. Integration of knowledge is a process/method/way to generate a comprehensive educational reform for the betterment of humankind. It should not be considered a new phenomenon as Muslims have embraced integration of religious and human sciences throughout Islamic history.